(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Violence affects all of us. So, I asked myself – what is the structure of this subject, violence? What are the elements therein? How does violence configure in various genres of literature, how does literature respond to violence? What are the literary possibilities of literature on on violence and what kind of exploration is to be made in the context?The word ‘violence’ came in English language via Old French from Latin ‘Violentia’ which refers to behaviour involving physical fore or power intended to harm, damage or kill someone, or oneself or a group or a community. According to sociologists and legal experts, the use of unfair exercise of power or force broadens the scope of our conventional understanding of violence to include those acts which result from power relationships such as neglect or acts of omission or more obvious violent acts. But it is also true that violence against women, children or elderly does not always result in injury or death. Psychologists argue that sometimes its consequences become important. The consequences can be latent and last for years in the unconscious realm of human mind causing psychological and social damage. Therefore, we should understand the implications of experience of violence from several perspectives. If we examine literature of violence, we will find that various manifestations of states of violence represented in literature include, injury, death, fear, apprehension, dislocation, cruelty, depression, deprivation, painful projection, indifference and despondency.